An effective electrochemical sensor for monitoring tamoxifen as breast cancer medicine in biological samples using polypyrrole-based molecularly imprinted polymers and CNTs hybrid structure - Junwei Chen; Zhaoyu Chen; Yucheng Zheng; Wenying Chen; Qingjun Zhu; Peng Sun; Yao Chen (Sensing and Bio-Sensing Research)
This work was conducted on the development and characterization of a novel electrochemical sensor using polypyrrole-based molecularly imprinted polymer and CNTs hybrid-modified glassy carbon electrode (MIP/CNTs/GCE) for the determination of tamoxifen (TMX), a widely used breast cancer medicine, in biological samples. Characterization of the synthesized nanostructures using structural and morphological analyses confirmed the successful use of the MIP/CNTs hybrid and provided insights into the scaffolds' chemical and structural characteristics. Electrochemical analyses showed the enhanced performance of the MIP/CNTs/GCE sensor, which displayed a linear response range of 1 to 420 μM, sensitivity of 0.72337 μA/μM, and a detection limit of 0.01 μM for TMX. Reproducibility investigation exhibited an RSD of 2.96 %, and storage stability studies demonstrated that the electrochemical sensor retained 96.82 % of its initial response after 40 days. Moreover, the MIP sensor showed great selectivity for TMX in the presence of potential interferents and received recovery rates of 98.20 % to 99.10 % in human serum specimens. The findings show that the designed MIP/CNTs/GCE sensor can monitor TMX in complicated biological matrices in a reliable and effective manner.